KORELASI ANTARA POLA ASUH DEMOKRATIS DENGAN PRESTASI BELAJAR SISWA SMP - Ria Wulandari; Zaki Nur Fahmawati (Jurnal Mahasiswa BK An-Nur : Berbeda, Bermakna, Mulia, 2023)
This study aims to determine the relationship between democratic parenting and learning achievement of junior high school students in Gempol sub-district. This research method uses a correlational quantitative approach. The analysis technique used the spearman correlation test with the help of IBM SPSS 22. The sample used in this study was 346 students using random sampling technique. Data collection using questionnaires and student report cards. The results of this study indicate that there is a positive relationship between democratic parenting and student learning achievement. In addition, the R value is 0.028, so it can be concluded that parenting patterns have an influence of 28% on student learning achievement, while the remaining 72% is influenced by other variables that are not studied.